Organizational behavior : - McShane, Steven Lattimore (McGraw-Hill, 2007)
Organizational Behavior [essentials] offers the same quality of contemporary knowledge, excellent readability, and classroom support that has made the hardback book by the same author team one of the best-selling OB books around the world - but in a smaller package. It applies four fundamental principles: linking theory with reality, organizational behavior for everyone, contemporary theory foundation, and active learning support. McShane and Von Glinow have sliced out the extended or secondary topics so students can drill down to what is really essential. Although this book is less than two-thirds the length of their comprehensive hardback textbook, it doesn’t skimp on classroom support. In this era of active learning, critical thinking, and outcomes-based teaching, these supplements are becoming more "essential" than ever